A Mobile App Development for E-Waste ‎Management in Bahrain (Athar)‎‎ - Ehab Juma Adwan; Noor Mohamed; Hayat Bureshaid; Batool Mohamed (Universitas Dian Nuswantoro, 2024)
Bahrain still suffers from electronic solid waste annually due to ineffective waste ‎disposal management. Compared to other Gulf Cooperation Council (GCC) countries, Bahrain ‎generates the largest waste quantity per person, approximately 1.2 to 1.8 ‎million tons of hazardous waste annually. Therefore, the present research article aims to manage the e-waste discarding mitigation by arranging the waste collection, ‎presenting it for sale/purchase/donation (C2C, C2B, B2G), and organizing the waste recycling ‎process. Derived from this aim, the article explores the e-waste ‎phenomena and proposes the development of an e-waste mobile application named “Athar”. ‎ The significance of “Athar” lies in firstly, enabling citizens to live in a ‎clean environment with limited diseases. Secondly, assisting the ‎Ministry of Tourism attract more tourists. ‎ The research article embraces a seven-phased Agile-based SDLC method to analyze, design, implement, test, and evaluate Athar through the utilization of several research techniques, including questionnaires to collect user and system requirements, other techniques such as data flow diagrams, entity relationship diagram, ‎database schema, etc. for the system design, ‎OutSystems programming language to implement the mobile app, and one questionnaire based on ‎Nielsen heuristics for usability evaluation. Findings demonstrate the adequacy of the Athar application with an outstanding usability score of 89.1%.